CHANGE OF DYNAMICS OF SALES AND IMPORT OF MOTOR VEHICLES IN THE RUSSIAN MARKET UNDER THE INFLUENCE OF INSTABILITY OF THE EXTERNAL ENVIRONMENT - A. Pasko (Вестник университета)
The situation with imposition of economic sanctions of the west countries West to Russia affected also on development of the Russian market of motor vehicles. In the article key parameters and the prospects of development of the Russian motor vehicles market (including its import component) in the conditions of the unstable external environment are generalized and analysed.